Human Rights in The Digital Era: Online Privacy, Freedom Of Speech, and Personal Data Protection - Siagian, Riduan; Leonard Siahaan; Muhammad Ichwan Hamzah (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This study analyzes the impact of digital technology on human rights in the modern context. The main focus is on online privacy, freedom of speech, and personal data protection. The research method is qualitative through a literature review and involves literature analysis to understand fundamental issues. This study highlights risks related to online privacy and questions regarding freedom of speech on social media. Additionally, the protection of personal data also takes a significant focus, with an emphasis on the need for appropriate regulations. Despite challenges, the digital era also brings opportunities for human rights campaigns and increased awareness. This research provides essential guidance for policies that can uphold the integrity of human rights in the ever-evolving digital era.